'A faint whiff of cigar': the literary tourist's experience of visiting writers' homes. Issue 9 (3rd May 2021) - MacLeod, Nicola
ABSTRACT: Places associated with authors and their literary creations are popular attractions and amongst the most compelling of these literary tourism sites are writers' homes where visitors can gain personal insights into their favourite artists. However, there are few studies on the experience of literary tourists in these settings and this paper addresses this gap by analysing 1200 TripAdvisor reviews of four well-known English and American literary homes using Leximancer software which uses a quantitative approach to carry out qualitative analysis of text. The conceptual framework of the genius loci was used to inform this analysis of the literary visitor experience. The findings revealed that for these literary visitors, the domestic setting was the most important aspect of the visit, coupled with the knowledge gained and the experience of being in proximity to the creative process itself. Further thematic analysis also revealed that visitors were keen to seek out authentic, personal objects and sensed the presence of the deceased author within the house. The article concludes that the notion of the genius loci – the presiding spirit of place – is a useful way of conceptualizing the literary visitor's experience of author's homes and informing their presentation and management as visitor attractions.